Preparation method of porous anode support body

By using silica as a pore-forming agent in the nickel-based anode support and using hydrofluoric acid dissolution technology to prepare a porous anode support with uniform pore structure, the problem of uneven pore structure in the prior art is solved, and the output power and stability of SOFC are significantly improved.

CN119775026AActive Publication Date: 2025-04-08PILOT THIN FILM MATERIALS (ZIBO) CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411774552.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-04-08
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

The pore structure of the existing nickel-based anode support is uneven, resulting in low gas transmission and diffusion efficiency, affecting the output power and stability of SOFC.

Method used

Silica is used as the pore-forming agent and dissolved by hydrofluoric acid to prepare a porous anode support with uniform pore distribution, high porosity and interconnected.

Benefits of technology

It improves the gas transmission and diffusion ability, increases the three-phase interface of electrochemical reactions, reduces the concentration difference polarization, thereby improving the output power density and operating stability of SOFC.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775026A_ABST
    Figure CN119775026A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a porous anode support, which is characterized by comprising the following steps: S1, carrying out ball milling on nickel oxide, zirconium oxide, silicon dioxide, a solvent and an adhesive to obtain ball-milled slurry; drying the ball-milled slurry to obtain mixed powder; s2, tabletting the mixed powder prepared in the step S1, and then discharging glue and sintering to obtain an anode support intermediate; s3, the anode support intermediate prepared in the step S2 is placed in a hydrofluoric acid solution for soaking and silicon dissolving, and the anode support intermediate after silicon dissolving is obtained; and S4, carrying out secondary sintering on the silicon-dissolved anode support intermediate prepared in the step S3 to obtain the porous anode support. According to the invention, silicon dioxide is used as a pore-forming agent and is dissolved by hydrofluoric acid, and the prepared porous anode support body can increase a three-phase interface of electrochemical reaction and reduce concentration polarization, so that the output power density and the operation stability of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of solid oxide fuel cells, and in particular relates to a method for preparing a porous anode support. Background Art

[0002] Solid oxide fuel cell (SOFC) is a device that uses electrochemical reactions to directly convert the chemical energy of fuel gas into electrical energy. Unlike other fuel cells, SOFC uses all-solid-state components, mainly including a dense solid electrolyte layer, a porous anode layer and a porous cathode layer. For a complete SOFC single cell, in addition to the anode, cathode and electrolyte parts that play a functional role, a component that plays a structural support role is also required to ensure that the battery has sufficient mechanical strength for stable long-term operation. This part is the support. According to different support structures, SOFC is divided into electrolyte support, metal support and electrode support. Among them, electrolyte-supported SOFC developed the earliest, usually with an electrolyte with a thickness of 100 to 300 microns as a support. Because of its large ohmic loss, it mostly operates at high temperatures; the preparation process of metal-supported SOFC is complex and difficult, and relatively less researched; electrode-supported SOFC can be divided into cathode support and anode support. By thinning the electrolyte, the ohmic resistance caused by the electrolyte can be effectively reduced, so that SOFC can operate in the medium temperature range. The thicker cathode support causes larger polarization resistance and ohmic resistance, making cathode-supported batteries relatively uncommon, while anode supports usually adopt metal-ceramic structures with higher mechanical strength and electrical conductivity. Therefore, anode supports are the most widely used support type at present.

[0003] The nickel-based anode support has the characteristics of simple preparation process, low cost and high catalytic activity. Nickel oxide is the most advantageous anode support material in SOFC. In addition to having a certain strength, the anode support also needs to have a sufficiently high porosity to ensure that the fuel gas quickly diffuses to the three-phase reaction interface to participate in the reaction. At the same time, it should ensure that the gas can escape quickly after the reaction to reduce concentration polarization to obtain a higher output power density. In order to increase the porosity of the anode support, a certain amount of pore former is often added to the initial powder. The pore former volatilizes during the high-temperature sintering process of the battery and leaves pores to improve the microstructure of the anode support. The pore former of the traditional Ni-based composite ceramic anode support includes flour, starch, graphite, carbon powder, wood cellulose, paper fiber, etc. However, after the pore former is pyrolyzed, a tortuous gas channel is formed, which increases the path and length of gas transport, which is not conducive to the rapid migration and diffusion of gas. Therefore, how to further improve the pore structure of the nickel-based anode support and accelerate the migration and diffusion of gas is of great significance for improving the output power and stability of SOFC. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing a porous anode support having uniform pore distribution, high porosity and capable of forming interconnected pores.

[0005] In a first aspect, the present invention provides a method for preparing a porous anode support, which adopts the following technical scheme: A method for preparing a porous anode support comprises the following steps: S1: ball-milling nickel oxide, zirconium oxide, silicon dioxide, a solvent and a binder to obtain a ball-milled slurry; and drying the ball-milled slurry to obtain a mixed powder; S2: tableting the mixed powder prepared in step S1, followed by debinding and sintering to obtain an anode support intermediate; S3: placing the anode support intermediate prepared in step S2 in a hydrofluoric acid solution to soak and dissolve silicon, thereby obtaining an anode support intermediate after silicon is dissolved; S4: performing secondary sintering on the anode support intermediate after silicon dissolution prepared in step S3 to obtain a porous anode support.

[0006] Preferably, in step S1, the ratio of the mass of silicon dioxide to the total mass of nickel oxide and zirconium oxide is (2-8):(16-20).

[0007] Preferably, in step S1, the particle size of silicon dioxide is 200-400 nm.

[0008] Preferably, in step S1, the mass ratio of nickel oxide to zirconium oxide is (8-10):(8-10); The solvent is one or more of ethanol and butanone, and the ratio of the mass of the solvent to the total mass of nickel oxide and zirconium oxide is (15-30):(16-20); The adhesive is one or more of polyvinyl butyral and polyethyl methacrylate, and the total mass ratio of the adhesive to nickel oxide and zirconium oxide is (1-3):(16-20).

[0009] Preferably, in step S1, the ball milling is divided into two ball millings. The first ball milling is to mix nickel oxide, zirconium oxide powder, silicon dioxide and solvent and then ball mill them. After the first ball milling is completed, a binder is added to the slurry after the first ball milling for a second ball milling. After the ball milling is completed, a ball milled slurry is obtained.

[0010] Further preferably, the first ball milling time is 2-10 hours, and the ball milling speed is 50-100 rpm; the second ball milling time is 5-10 hours, and the ball milling speed is 50-100 rpm.

[0011] Preferably, in step S1, the drying temperature is 90-150° C., and the drying time is 5-15 hours.

[0012] Preferably, in step S2, the debinding temperature is 300-600°C, the debinding time is 2-6 hours, the sintering temperature is 900-1300°C, the sintering and heat preservation time is 1-5 hours, and the sintering heating rate is 2-8°C / min.

[0013] Preferably, in step S3, the concentration of hydrofluoric acid is 30-50wt%, and the immersion time is 1-4h.

[0014] Preferably, in step S4, the sintering temperature of the secondary sintering is 900-1300° C., the insulation time of the secondary sintering is 1-5 h, and the heating rate is 2-8° C. / min.

[0015] In a second aspect, the present invention provides a porous anode support, which is prepared by the aforementioned preparation method.

[0016] Beneficial effects of the present invention: (1) In the present invention, silicon dioxide is used as a pore-forming agent. After dissolving it with hydrofluoric acid, the pores on the prepared porous anode support are evenly distributed, have a high porosity, and can form interconnected pores, which are beneficial to the transmission and diffusion of gases, can increase the three-phase interface of the electrochemical reaction, and reduce concentration polarization, thereby improving the output power density and operation stability of the battery.

[0017] (2) In the present invention, hydrofluoric acid also has a slight etching effect on nickel oxide and zirconium oxide, so there will be pores formed by etching on the support skeleton of the porous anode support, thereby further improving the porosity while ensuring the strength of the substrate, thereby further improving the performance of the solid oxide fuel cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Process flow chart of the present invention.

[0019] Figure 2 These are microscopic morphology images of the surface (a) and cross section (b) of the nickel-based porous anode support in Example 1. DETAILED DESCRIPTION

[0020] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments. Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0021] The process flow chart of the present invention is as follows Figure 1 As shown, the specific preparation method can be seen in the embodiments.

[0022] Example 1 The method for preparing the nickel-based porous anode support in this embodiment comprises the following steps: S1 Ball milling: First add 9g nickel oxide, 9g zirconium oxide, 2g silicon dioxide (average particle size of 250nm), and 20g ethanol into a 1L ball mill, and carry out the first ball milling at a rotation speed of 100rpm for 2h. After the first ball milling, a primary slurry is obtained; add 2g PVB to the primary slurry, and carry out a second ball milling at a rotation speed of 100rpm for 5h. After the ball milling, a slurry is obtained; the slurry is placed in an oven and dried at 100℃ for 5h to obtain a mixed powder.

[0023] S2 Tableting, debinding and sintering: Place the mixed powder obtained in step S1 in a mold and perform tableting to obtain a disc with a diameter of 15 mm and a thickness of 0.5 mm. Place the disc in a muffle furnace for debinding and sintering. The debinding temperature is 400°C and the debinding time is 2h. The sintering temperature is 1200°C, the sintering holding time is 2h, and the sintering heating rate is 5°C / min. After sintering, an anode support intermediate is obtained.

[0024] S3 Dissolution: The anode support intermediate in step S3 is placed in 40 wt % hydrofluoric acid to soak and dissolve silicon for 2 hours to obtain an anode support intermediate after silicon dissolution.

[0025] S4 Sintering: The anode support intermediate after silicon dissolution in step S3 is placed in a muffle furnace, heated to 1200° C. at 5° C. / min, and sintered at this temperature for 2 h to obtain a nickel-based porous anode support.

[0026] The SEM image of the nickel-based porous anode support prepared in this example is as follows: Figure 2 As shown, the surface and cross section of the anode support are loose and porous, and the pore distribution on the surface and cross section is relatively uniform; Figure 2 (b) It can be seen that a small number of channels penetrate the entire support body to form through holes.

[0027] Example 2 Example 2 is substantially the same as Example 1, except that the amount of silicon dioxide added in step S1 of Example 2 is 4.5 g.

[0028] Example 3 Example 3 is substantially the same as Example 1, except that the amount of silicon dioxide added in step S1 of Example 3 is 7.7 g.

[0029] Comparative Example 1 The preparation method of the nickel-based porous anode support in this comparative example comprises the following steps: S1 Ball milling: First add 9g nickel oxide, 9g zirconium oxide, 4.5g graphite (average particle size of 250nm), and 20g ethanol into a 1L ball mill, and carry out the first ball milling at a rotation speed of 100rpm for 2h. After the first ball milling, a primary slurry is obtained; add 2g PVB to the primary slurry, and carry out a second ball milling at a rotation speed of 100rpm for 5h. After the ball milling, a slurry is obtained; the slurry is placed in an oven and dried at 100°C for 5h to obtain a mixed powder.

[0030] S2 Tableting, debinding and sintering: Place the mixed powder obtained in step S1 in a mold and perform tableting to obtain a disc with a diameter of 15 mm and a thickness of 0.5 mm. Place the disc in a muffle furnace for debinding and sintering. The debinding temperature is 400°C and the debinding time is 2h. The sintering temperature is 1200°C, the sintering holding time is 2h, and the sintering heating rate is 5°C / min. After sintering, an anode support is obtained.

[0031] Example 4 It is basically the same as Example 1, except that a stage of ball milling is performed in step S1, which is as follows: S1 Ball milling: First add 9g nickel oxide, 9g zirconium oxide, 2g silicon dioxide, 20g ethanol and 2g PVB into a 1L ball mill, and ball mill for 7h at a speed of 100rpm. Place the slurry after ball milling in an oven at 100℃ and dry it for 5h to obtain a mixed powder.

[0032] Example 5 It is basically the same as Example 2, except that the immersion time for silicon dissolution is 1 hour.

[0033] Example 6 It is basically the same as Example 2, except that the immersion time for silicon dissolution is 4 hours.

[0034] Example 7 The method for preparing the nickel-based porous anode support in this embodiment comprises the following steps: S1 Ball milling: First add 8g nickel oxide, 8g zirconium oxide, 6g silicon dioxide (average particle size is 220nm), and 25g ethanol into a 1L ball milling jar, and carry out the first ball milling at a rotation speed of 80rpm for 4h. After the first ball milling, a primary slurry is obtained; add 1g PVB to the primary slurry, and carry out a second ball milling at a rotation speed of 80rpm for 7h. After the ball milling, a slurry is obtained; the slurry is placed in an oven and dried at 90℃ for 10h to obtain a mixed powder.

[0035] S2 Tableting, debinding and sintering: Place the mixed powder obtained in step S1 in a mold and perform tableting to obtain a disc with a diameter of 15 mm and a thickness of 0.5 mm. Place the disc in a muffle furnace for debinding and sintering. The debinding temperature is 300°C and the debinding time is 4 hours. The sintering temperature is 900°C, the sintering holding time is 5 hours, and the sintering heating rate is 3°C / min. After sintering, an anode support intermediate is obtained.

[0036] S3 Dissolution: The anode support intermediate in step S3 is placed in 30 wt % hydrofluoric acid to soak and dissolve silicon for 3 hours to obtain an anode support intermediate after silicon is dissolved.

[0037] S4 Sintering: The anode support intermediate after silicon dissolution in step S3 is placed in a muffle furnace, heated to 900° C. at 5° C. / min, and sintered at this temperature for 5 h to obtain a nickel-based porous anode support.

[0038] Example 8 The method for preparing the nickel-based porous anode support in this embodiment comprises the following steps: S1 Ball milling: First add 10g nickel oxide, 10g zirconium oxide, 5g silicon dioxide (average particle size of 300nm), and 30g ethanol into a 1L ball mill, and carry out the first ball milling at a rotation speed of 50rpm for 8h. After the first ball milling, a primary slurry is obtained; add 3g PVB to the primary slurry, and carry out a second ball milling at a rotation speed of 50rpm for 8h. After the ball milling, a slurry is obtained; the slurry is placed in an oven and dried at 120°C for 5h to obtain a mixed powder.

[0039] S2 Tableting, debinding and sintering: Place the mixed powder obtained in step S1 in a mold and perform tableting to obtain a disc with a diameter of 15 mm and a thickness of 0.5 mm. Place the disc in a muffle furnace for debinding and sintering. The debinding temperature is 500°C and the debinding time is 2h. The sintering temperature is 1300°C, the sintering holding time is 1h, and the sintering heating rate is 7°C / min. After sintering, an anode support intermediate is obtained.

[0040] S3 Dissolution: The anode support intermediate in step S3 is placed in 50 wt % hydrofluoric acid to soak and dissolve silicon for 1 hour to obtain an anode support intermediate after silicon is dissolved.

[0041] S4 Sintering: The anode support intermediate after silicon dissolution in step S3 is placed in a muffle furnace, heated to 1300° C. at 7° C. / min, and sintered at this temperature for 1 hour to obtain a nickel-based porous anode support.

[0042] The porosity, flexural strength and electrochemical performance tests were performed on Examples 1 to 8 and Comparative Example 1 of the present invention. The specific test methods are as follows: The porosity is measured using the Archimedean method. The specific test steps are as follows: first test the mass m1 of the sample when it is dry, then place the sample in a beaker filled with deionized water, and place the beaker on an electric stove to boil for 3 hours. After the temperature drops to room temperature, wipe off the water on the surface of the sample with weighing paper, and weigh the mass m2 of the saturated sample in the air. Next, place the saturated sample in a tray, hang the tray on the bottom of the balance with a homemade wire, and immerse the tray in a beaker filled with water, and weigh the mass m3 of the saturated sample in water. Finally, the porosity q of the sample is calculated using the formula: 2. The method of flexural strength test is as follows: During the test, the sample to be tested is fixed on the sample table, and the external load is applied by the universal testing machine. The bending strength of the sample is calculated by the formula. The calculation formula of bending strength is: σ=(FL) / (wd 2 ) Where: σ represents the material strength, in MPa; F represents the maximum force applied; L represents the length of the sample; w represents the width of the sample; d represents the thickness of the sample.

[0043] 3. The electrochemical performance test includes the following steps: Preparation of YSZ electrolyte: Preparation of YSZ electrolyte slurry: Weigh 0.75g PVB and 10g anhydrous ethanol in a beaker, seal it and put it in a 60°C oven. Wait until the PVB in the solution is completely dissolved and the solution becomes viscous to obtain a PVB-ethanol solution.

[0044] Weigh 15 g YSZ, 45 g anhydrous ethanol, 0.75 g DOP (dioctyl phthalate), 0.75 g TEA (triethanolamine) and 0.75 g PEG into a ball mill. After ball milling for 3 h, add PVB-ethanol solution and continue ball milling for 2 h to obtain a uniform YSZ electrolyte slurry.

[0045] The YSZ electrolyte membrane was prepared on the surface of the NiO-YSZ anode support by an immersion method. The specific operation steps were as follows: one side of the nickel-based porous anode support was glued with double-sided tape and then placed on the top of a corundum tube; YSZ electrolyte slurry was added to a beaker (the depth of the slurry needed to be greater than the thickness of the anode support), and then the other side of the nickel-based porous anode support (the side without the double-sided tape) was completely immersed in the slurry. After 10 seconds, the nickel-based porous anode support was taken out of the YSZ slurry, and the nickel-based porous anode support was rotated at a constant speed to make the electrolyte slurry on its surface evenly distributed, and then the excess slurry was sucked away with a cotton swab, and the electrolyte layer was allowed to stand for 15 minutes. The above steps were repeated twice to obtain an electrolyte layer; finally, the nickel-based porous anode support impregnated with the electrolyte layer was placed in a high-temperature muffle furnace, sintered at 1500 ° C for 4 hours, and after cooling to room temperature, a nickel-based porous anode support material composited with an electrolyte layer was obtained.

[0046] Preparation of LSM-YSZ and LSM cathode slurries Preparation of LSM cathode slurry: 15 g of pineneol and 1.5 g of PVB were placed in a clean beaker, sealed and placed in a 60°C oven until the PVB in the solution was completely dissolved and the solution became viscous, thereby obtaining a PVB-pineneol solution.

[0047] 7.5g LSM powder and 15g anhydrous ethanol were placed in a ball mill, and after ball milling for 2h, the mixture was uniformly mixed into a slurry; the slurry was heated and evaporated to dryness to obtain ball-milled LSM powder. 3g PVB-terpineol solution and 2g LSM powder were placed in a mortar and fully ground for 2h to obtain LSM cathode slurry.

[0048] Preparation of LSM-YSZ composite cathode slurry: Weigh 2g YSZ powder and 2.5g LSM powder in a ball mill, add 15g anhydrous ethanol, and ball mill for 2 h to obtain a slurry. Heat the slurry and evaporate it to dryness to obtain LSM-YSZ composite powder. Place 2.5g PVB-terpineol solution and 2g LSM-YSZ composite powder in a mortar and grind them thoroughly for 2h to obtain LSM-YSZ composite cathode slurry.

[0049] Preparation of SOFC cathode: LSM-YSZ composite cathode slurry is coated on the electrolyte layer of the nickel-based porous anode support material composited with the electrolyte layer, with a coating thickness of 20μm; then dried in an oven at 120°C for 15min; the coating is repeated again according to the process; a composite LSM-YSZ composite cathode-electrolyte layer-anode support material is obtained.

[0050] According to the preparation method of the LSM-YSZ composite cathode, an LSM cathode layer was prepared on an LSM-YSZ composite cathode of a composite LSM-YSZ composite cathode-electrolyte layer-anode support material, and then sintered at 1100° C. for 3 hours to obtain a SOFC single cell.

[0051] Battery performance test The assembled SOFC single cell was placed in a tubular heating furnace for heating. Hydrogen was used as fuel. All cell performances were tested at 750-850°C using an IM6ex electrochemical workstation. The test voltage range was 0-1.2 V and the voltage scan rate was 5 mV s -1 , the test frequency range is 0.1 to 106 Hz, the disturbance voltage is 10 mV; the IV cycle curve is measured, and the maximum voltage and maximum current are read from the IV cycle curve; the maximum power density of the battery is calculated according to the following formula.

[0052] The test results of the porosity and flexural strength of the anode supports prepared in Examples 1-8 and Comparative Example 1 are shown in Table 1; the test results of the maximum power density of the SOFC cell assembled from the anode supports are also shown in Table 1.

[0053] Table 1 The main difference between the preparation methods of Examples 1 to 3 is the amount of silicon dioxide added. From the test results, the more silicon dioxide is added, the higher the porosity of the nickel-based porous anode support and the lower the bending strength; the maximum power density of the assembled SOFC battery increases first and then decreases. All of Examples 1 to 3 have good performance. Overall, Example 2 has the best effect.

[0054] Only one stage of ball milling was performed in the preparation method of Example 4. Overall, the comprehensive performance of the nickel-based porous anode support prepared by one stage of ball milling in Example 4 was lower than that of the nickel-based porous anode support prepared by two stages of ball milling in Example 2.

[0055] In the preparation methods of Examples 2, 5 and 6, the main difference is the immersion time of silicon dissolution. From the data, the longer the immersion time, the higher the porosity of the nickel-based porous anode support and the lower the bending strength; the maximum power density of the assembled SOFC battery increases first and then decreases according to the immersion time. Examples 2 and 5 have better performance, and Example 6 may have a greater performance decline due to excessive damage to the matrix of the nickel-based porous anode support during the immersion time.

[0056] Compared with Comparative Example 1, the porosity of the nickel-based porous anode support prepared in Example 2 and the maximum power density of the battery are significantly better than those of the nickel-based porous anode support prepared in Comparative Example 1.

[0057] Examples 7 and 8 mainly involve the adjustment of process parameters in the preparation method, and the performance of the nickel-based porous anode supports prepared therefrom will also have certain fluctuations; but overall, the nickel-based porous anode supports prepared in Examples 7 and 8 still have good comprehensive performance.

[0058] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a porous anode support, characterized in that: The following steps are involved: S1: ball-milling nickel oxide, zirconium oxide, silicon dioxide, a solvent and a binder to obtain a ball-milled slurry; and drying the ball-milled slurry to obtain a mixed powder; S2: tableting the mixed powder prepared in step S1, followed by debinding and sintering to obtain an anode support intermediate; S3: placing the anode support intermediate prepared in step S2 in a hydrofluoric acid solution to soak and dissolve silicon, thereby obtaining an anode support intermediate after silicon is dissolved; S4: performing secondary sintering on the anode support intermediate after silicon dissolution prepared in step S3 to obtain a porous anode support.

2. The method for preparing a porous anode support according to claim 1, characterized in that: In step S1, the ratio of the mass of silicon dioxide to the total mass of nickel oxide and zirconium oxide is (2-8):(16-20).

3. The method for preparing a porous anode support according to claim 1 or 2, characterized in that: In the step S1, the particle size of the silicon dioxide is 200-400 nm.

4. The method for preparing a porous anode support according to claim 1, characterized in that: In the step S1, the mass ratio of nickel oxide to zirconium oxide is (8-10):(8-10); The solvent is one or more of ethanol and butanone, and the ratio of the mass of the solvent to the total mass of nickel oxide and zirconium oxide is (15-30):(16-20); The adhesive is one or more of polyvinyl butyral and polyethyl methacrylate, and the total mass ratio of the adhesive to nickel oxide and zirconium oxide is (1-3):(16-20).

5. The method for preparing a porous anode support according to claim 1, characterized in that: In the step S1, the ball milling is divided into two ball millings. The first ball milling is to mix nickel oxide, zirconium oxide, silicon dioxide and solvent and then ball mill them. After the first ball milling is completed, a binder is added to the slurry after the first ball milling for a second ball milling. After the ball milling is completed, a ball milled slurry is obtained.

6. The method for preparing a porous anode support according to claim 4, characterized in that: The first ball milling time is 2-10 hours, and the ball milling speed is 50-100 rpm; the second ball milling time is 5-10 hours, and the ball milling speed is 50-100 rpm.

7. The method for preparing a porous anode support according to claim 1, characterized in that: In the step S2, the debinding temperature is 300-600°C, and the debinding time is 2-6 hours; the sintering temperature is 900-1300°C, the sintering and heat preservation time is 1-5 hours, and the sintering heating rate is 2-8°C / min.

8. The method for preparing a porous anode support according to claim 1, characterized in that: In step S3, the concentration of hydrofluoric acid is 30-50 wt %, and the immersion time is 1-4 h.

9. The method for preparing a porous anode support according to claim 1, characterized in that: In the step S4, the sintering temperature of the secondary sintering is 900-1300° C., the insulation time of the secondary sintering is 1-5 hours, and the heating rate is 2-8° C. / min.

10. A porous anode support, characterized in that: The porous anode support is prepared by the preparation method described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of multihole anode support of solid oxide fuel cell

    CN103236548A

  • Porous gas diffusion layer and preparation method thereof

    CN104779399A

  • Three-dimensional porous material and preparing method thereof

    CN105347835A

  • Silicon-containing mineral-based porous silicon-carbon composite negative electrode material and preparation method thereof

    CN113871604A

  • Porous lithium lanthanum zirconium oxide solid electrolyte sheet as well as preparation method and application thereof

    CN115466116A